2009
DOI: 10.1021/ja900244x
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Induced Folding of Diels−Alderase Ribozymes Studied by Static and Time-Resolved NMR Spectroscopy

Abstract: The metal ion-induced folding of the Diels-Alder ribozyme into a catalytically active form with a complex RNA pseudoknot has been characterized by static and time-resolved NMR spectroscopy. The conformations of two sequences from the Diels-Alder ribozyme family, A27 WT and G27 MUT, were studied in the absence and presence of metal ions and of ligand. The single nucleotide mutant G27 MUT in the absence of metal ions displayed conformational heterogeneity which greatly influences its folding trajectory. Time-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 55 publications
3
28
0
Order By: Relevance
“…The possibility to disassemble the catalytic pocket by breaking a single hydrogen bond may be important for the multiple-turnover behavior of this catalyst (8,9), and also for the possibility of a ‘back door’ reaction pathway that requires substrate passage through a narrow orifice (29). Such a frequent breakdown and re-formation of the tertiary structure would be consistent with the structural transitions between ‘folded’ and ‘intermediate’ conformations on the 100 ms timescale, which were observed by both single-molecule (12) and NMR spectroscopy (13). …”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The possibility to disassemble the catalytic pocket by breaking a single hydrogen bond may be important for the multiple-turnover behavior of this catalyst (8,9), and also for the possibility of a ‘back door’ reaction pathway that requires substrate passage through a narrow orifice (29). Such a frequent breakdown and re-formation of the tertiary structure would be consistent with the structural transitions between ‘folded’ and ‘intermediate’ conformations on the 100 ms timescale, which were observed by both single-molecule (12) and NMR spectroscopy (13). …”
Section: Discussionsupporting
confidence: 72%
“…Single-molecule fluorescence resonance energy transfer (smFRET) and nuclear magnetic resonance (NMR) spectroscopy have revealed that the ribozyme is highly dynamic in aqueous solution at room temperature (12,13). The concentration of divalent metal ions was established as a major determinant of folding and dynamics (12–14).…”
Section: Introductionmentioning
confidence: 99%
“…4 Therefore, catalysis may not be decoupled from RNA folding. This latter process is hierarchical, first proceeding on the secondary structure level via formation of fairly stable Watson–Crick base pairs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nucleobase carbon (C2, C5, C6, and C8) and proton (H2, H5, H6, and H8) chemical shifts are increasingly being used in defining the 3D structures of RNA and DNA (Wijmenga et al 1997; Cromsigt et al 2001; Xu and Case 2001; Barton et al 2013; Frank et al 2013; Frank et al 2013; Sahakyan and Vendruscolo 2013; Werf et al 2013; Sripakdeevong et al 2014). Having the ability to acquire these chemical shift data rapidly would be important for applications ranging from nucleic acid targeted ligand screening to time-resolved NMR studies of biochemical processes such as catalysis (Buck et al 2009) and folding (Wenter et al 2005; Buck et al 2007; Manoharan et al 2009; Lee et al 2010; Lieblein et al 2012; Li et al 2014). In addition, L-optimization for aromatic protons has been successfully implemented to measure residual dipolar couplings for nucleic acids (Ying et al 2011).…”
mentioning
confidence: 99%